Inovação em rede de PMEs: fatores determinantes e consequências sociais - Sakamoto, Angela Ruriko (2011)
This study aimed to investigate how innovation emerges as a result of interactions among firms in a collaborative network of micro, small and medium enterprises (SMEs) in the furniture sector of metropolitan area in São Paulo, the Movelaria Paulista. Innovation in collaborative networks of SMEs in emerging economies has been influenced by various entities, especially the government, and the theme of innovation is usually studied at the firm level, focusing on innovation processes and product development. Innovation as much as network theory has a strategic bias in order to increase performance, competitiveness, share information and to reduce uncertainty and market´s ambiguity. Moreover, SMEs are recognized as organizations that have limited resources (human and financial) and low inclination to strategic planning. However, the Movelaria Paulista network has innovated consistently since its formation in 2004. To explain this complex phenomenon – innovation in network of small businesses, in an emerging country with weak institutions, which belongs to a traditional industry with low use of technology – and not fully covered by the theoretical field, this research was conducted using the Grounded Theory, in order to come up with a substantive theory to explain this phenomena by stand point of involved ones. The Movelaria Paulista is the object of this research and is composed of 52 companies and employs around 1,700 people. During the data collection were performed 45 interviews, 36 factories visited and it was attended six internal meetings as an observer and in two open forums to the public. In addition to almost 3,700 minutes of interviews, it was gathered several secondary data such as magazines, articles and reports. The results enabled to understand the network dynamics of collaboration that results in innovation, and the most revealing contribution is the transformation impact that Movelaria produces in its social context. The projects conducted in Movelaria Paulista foster collaboration within the group and inspire its members to promote internal changes in the organization, which in turn affect its employees and the community around. This pro collective guidance explains the support provided to the improvement of each member and the whole furniture sector as well. This behavior increases the members’ earnings perception in being part of the network, which include and integrate its members, attract new external actors, who foster new opportunities for innovation by increasing the creative space and building bridges to shorten the access to new knowledge. The results have also practical implications for Movelaria to face their challenges and for the institutions to rethink their role in order to increase their aggregated value to this network and to the others.